THEORETICAL FOUNDATIONS OF SUSTAINABLE DEVELOPMENT OF RURAL AREAS (TOGO) - Malacoubame , K.; Hanchar , A. (EurasianUnionScientists, 2021)
The conservative approach to development sustainability focuses primarily on the preservation of resources and transmitting them to future generations, while at the same time the main objective of the system is to reproduce and renew the natural resources already used. The evolutionary approach; considers a development from the perspective that global changes are occurring in the environment. It consists of making adjustments, which in turn will allow the evolution of the trajectory of society as a whole.